Synthesis and Study of Luminescent Materials on the Basis of Mixed Phosphates - Malygin, Vitalii V.; Lebedev, Lev A.; Bakhmetyev, Vadim V.; Keskinova, Mariia V.; Sychov, Maxim M.; Mjakin, Sergey V.; Nakanishi, Yoichiro (Recent Global Research and Education: Technological Challenges, 2016)
Highly dispersed NaBaPO4:Eu3+ and NaBaPO4:Eu2+ phosphors were prepared using sol-gel and self-propagating high temperature synthesis routes. The effects of thermal treatment and dopant concentration on phase composition, crystallite size, lattice parameters and luminescent properties of the synthetized phosphors are studied. Using excitation and emission spectra, energy-level positions of luminescent centers were determined. The obtained phosphors provide an effective luminescence upon either UV or X-ray excitation that makes them promising for the application as components of white LEDs and medicine.